Profile of Inquiry Ability of Yogyakarta Junior High School Student in Biology Science Learning - Asri Widowati; Sukarni Hidayati (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2018)
Inquiry in science-Biology learning is very important for junior high school students because by inquiry, science learning can be oriented to processes and products. This study aims to: determine the achievement of the ability of  junior high school students in learning science-biology. This study uses descriptive research method to describe the inquiring ability of students based on the actual condition during research. The research subjects were junior high school students of class VII and VIII. The research instrument used was a test to measure the ability of individuals, the observation sheet in order to measure the inquiring ability of students, and a questionnaire as supporting data. Data were analyzed descriptively. The results of the study shown the achievement of students' abilities in general for each inquiring aspect of the students which is still in a fairly good category. Most students ( 60%) have the ability to record the observations result and the ability to make questions well. The achievement of students’ inquiring ability have not been optimum because the teacher experiences obstacles, as follow: giving treatment to emerge symptoms, finding specific symptoms of objects, finding problems, formulating problems, finding relationships among natural phenomena, tracking answers to problems based on observed symptoms, organizing data, analyzig data, interpreting data, finding and formulating problems to be applied in learning, and designing inquiry learning strategies.